Family Communication in Mixed Marriage Couples Between Indonesia-Australia - Albert Donatius Sirait; Noor Efni Salam; Yasir (UIR Press, 2020)
The way each person communicates depends on culture; language, rules, and norms of each. Culture has the responsibility for all communicative behavior and meaning that everyone has. Communication difficulties faced by the individuals involved are caused by differences in their respective cultural expectations. Differences in cultural expectations can lead to fatal risks, one of which is a misunderstanding. In intermarried family life there will be a misunderstanding of intercultural communication, which involves all family members. This situation can lead to an agreement to recognize one culture that will dominate or develop another culture which is a fusion of the two cultures (third culture), or even both cultures can go together in one family. This study discusses family communication in mixed marriage couples between Indonesia and Australia. The research carried out is intended to find out and analyze the negotiation of self-identity in interactions, conflict management mediated by face and culture, family communication processes, inhibiting factors, and supporting family communication in mixed marriage couples between Indonesia and Australia. Using advanced negotiation theory and symbolic interaction theory. In this study, the authors used a descriptive qualitative method. The data collection techniques used are through observation, interviews, and documentation. Data obtained shows that Mindfulness: Acceptance of new cultures, in terms of language (using both languages), nature (Australia: Individualism-Indonesia: collectivism). Mindlessness: Stereotype, perspective, building tolerance, dealing with habits, opening up to accept a new culture.